Central ghrelin increases anxiety in the Open Field test and impairs retention memory in a passive avoidance task in neonatal chicks - Caravajal, Pedro (2009)
Ghrelin (Grh) is an endogenous ligand for the growth hormone secretagogue receptor. Although Ghr stimulates feeding in rats, it inhibits feeding in neonatal chicks. However, little is known about other central behavioral effects of Ghr. Therefore, we investigated the Ghr effects, injected intracerebroventricularly, on anxiety and memory retention of neonatal chicks in an Open Field test and in a one-trial passive avoidance task, respectively. In the Open Field test, the administration of Ghr in a dose-dependent manner increased the latency to ambulate but decreased ambulation activity, indicating an anxiogenic effect. Furthermore, chicks trained on a passive avoidance task and injected with a dose of 30 pmol of Ghr immediately after training showed an impairment of memory retention. However, there were no significant effects on the number of pecks during the pretraining, training, retention and discrimination. In addition, different doses of Ghr produced an inhibition in food intake at different times after injection. Our results indicate that Ghr induces anxiogenesis in chicks. Moreover, we have shown for the first time that Ghr can decrease memory retention in a non-mammalian species, suggesting that Ghr may play an important role in the processes of memory retention in birds.